Copper oxide nanowires as better performance electrode material for supercapacitor application - Yar, A. (American Institute of Physics Inc., 2016)
Supercapacitors are highly attractive energy storage devices which are capable of delivering high power, with fast charging and long cycle life. Carbon based material rely on physical charging with less capacitance while metal oxide store charge by fast redox reaction with increased capacitance. Among metal oxide, copper oxide compounds are widely use in the form of nano and micro structures with no definite control over structure. In this work we utilized the well-controlled structure copper wires, originated from AAO template. Such well controlled structure offer better capacitance values due to easily excess of ions to the surface of wires. Performance of material was check in 3 M of potassium hydroxide (KOH). Specific capacitance (Cs) was calculated by using cyclic voltammetry (CV) and Charge discharge (CDC) test. The capacitance calculate on base on CV at 25 mV/s was 101.37 F/g while CDC showed the capacitance of 90 F/g at 2 A/g. Â© 2016 Author(s).